2014
DOI: 10.1097/pas.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features of Pediatric Oligodendrogliomas

Abstract: Oligodendrogliomas are an important adult form of diffuse gliomas with a distinctive clinical and genetic profile. Histologically similar tumors occurring rarely in children are incompletely characterized. We studied 50 patients with oligodendrogliomas (median age at diagnosis 8 y, range 7mo to 20 y). Tumors resembling dysembryoplastic neuroepithelial tumors or pilocytic astrocytomas or those having a “mixed” histology were excluded. Tumors at first diagnosis were low grade (n=38) or anaplastic (n=12). Histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…Extracortical tumors were associated with the worst prognosis of any region in the CNS in pODG. Rodriguez et al [21] also note the tendency of pODG to develop in extracortical regions rarely associated with adult disease. Peters et al [25] further report 9 of 32 cases analyzed appearing in these extracortical regions and note that such cases were associated with a significantly worse survival.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Extracortical tumors were associated with the worst prognosis of any region in the CNS in pODG. Rodriguez et al [21] also note the tendency of pODG to develop in extracortical regions rarely associated with adult disease. Peters et al [25] further report 9 of 32 cases analyzed appearing in these extracortical regions and note that such cases were associated with a significantly worse survival.…”
Section: Discussionmentioning
confidence: 99%
“…This result is supported in the pediatric neuro-oncology literature as well. Creach et al [22] identified 80% of 37 pODG cases as low grade while Rodriguez et al [21] identified 76% of 50 pODG cases as low grade. It is also important to highlight our finding that the improved survival seen in children compared with adults with oligodendroglioma applies only to low-grade tumors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations